Cell-type specific repertoire of responses to natural scenes in primate retinal ganglion cells - Kling, Alexandra; Brackbill, Nora; Rhoades, Colleen; Gogliettino, Alex; Sher, Alexander; Litke, Alan; Chichilnisky, E. J. (Frontiers in Cellular Neuroscience, 2025)
At least 20 distinct retinal ganglion cell (RGC) types have been identified morphologically in the primate retina, but our understanding of the distinctive visual messages they send to various targets in the brain remains limited, particularly for naturalistic stimuli. Here, we use large-scale multi-electrode recordings to examine how multiple functionally distinct RGC types in the macaque retina respond to flashed natural images. Responses to white noise visual stimulation were used to functionally identify 936 RGCs of 12 types in three recordings. Each cell type was confirmed by the mosaic organization of receptive fields, and seven cell types were cross-identified between recordings. Responses to thousands of natural images were used to examine the average firing rate kinetics in each RGC type as well as the repertoire of distinct firing patterns that each type produced. The average response across images was highly stereotyped for cells of each type and distinct for cells of different types. The responses to natural images more clearly distinguished certain cell types than did the response to white noise stimulation. Moreover, the full repertoires of firing patterns produced by different cell types, assessed by their latency and duration, were largely distinct in most cases and in some cases non-overlapping. Together these data provide an overview of the diversity of RGC signals transmitted from the primate retina to the brain in natural viewing conditions.